Magnetic Levitation Type Double Helix Self‐Powered Acceleration Sensor Based on ZnO‐RTV Film. Issue 1 (15th September 2021) - Mu, Jiliang; Han, Xiaotao; Yu, Junbin; Song, Jinsha; He, Jian; Geng, Wenping; Zou, Jie; Xian, Shuai; Chou, Xiujian
Abstract: Traditional accelerometers rely on batteries to provide energy, and the massive use of batteries caused great pressure on the natural environment. In this paper, a self‐powered acceleration sensor is designed. To more easily harvest weak vibration signals and effectively improve the sensitivity, this sensor is built on a magnetic levitation type double helix structure and ZnO‐doped triboelectric film. Experiments indicated that the open‐circuit voltage and short circuit current of the triboelectric nanogenerator (TENG) doped with ZnO are increased by 2.51 times and 2.07 times, respectively. Under shaking table test for simulating machine vibration environment, the sensor's sensitivity reaches 16.31 V (m s −2 ) −1 and its linearity is 0.993. The sensor power generation is 110 μW and its test range is ≈1–7 m s −2 . Also, the sensor can be applied for monitoring human's movement state by installing in a sole. This design provides a new idea for the development of TENG‐based sensors. Abstract : A self‐powered acceleration sensor is reported. To more easily harvest weak vibration signals and effectively improve the sensitivity, this sensor is built on a magnetic levitation type double helix structure and ZnO‐doped triboelectric film. The sensor's sensitivity and linearity are 16.31 V (m s −2 ) −1 and 0.993, respectively. It can be used for long‐term monitoring of machinery or human body.